Skijor with your dog - Høe-Raitto, Mari, 1959- (Book collections on Project MUSE., 2012)
Skijoring, or being pulled on skis by a dog in harness, is a great sport in which almost everyone-and almost any breed of dog-can participate. It requires little beyond a pair of skis and a dog with a desire to pull. The second edition of this popular and practical guide to the sport covers what equipment is needed, how to teach a dog to pull, and how to work with your dog year-round. Although it is geared toward beginners, Skijor with Your Dog offers plenty of useful information for experienced skijorers as well, including racing tips, how to involve children, how to camp and travel with dog.